2020
DOI: 10.1111/jop.13064
|View full text |Cite
|
Sign up to set email alerts
|

Is oral dysaesthesia a somatic symptom disorder?

Abstract: Oral dysaesthesia is a condition characterised by persistent alteration to oral sensation, perceived by the patient to be abnormal and unpleasant, in the absence of mucosal pathology. Its aetiology remains uncertain. The condition was attributed as a psychosomatic disease for much of the 20th century, but with newer technologies, recent literature has mostly focused on a possible peripheral or central neuropathic aetiology to oral dysaesthesia. Despite this, psychotropic medications and psychological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Oral dysesthesia is defined as an abnormal sensation in the oral cavity, such as a burning feeling, that is not associated with any abnormal clinical findings [53]. It is often described as a subjective feeling of oral tingling or pain, and it can be a diagnostic challenge for many clinicians.…”
Section: Oral Dysesthesiamentioning
confidence: 99%
“…Oral dysesthesia is defined as an abnormal sensation in the oral cavity, such as a burning feeling, that is not associated with any abnormal clinical findings [53]. It is often described as a subjective feeling of oral tingling or pain, and it can be a diagnostic challenge for many clinicians.…”
Section: Oral Dysesthesiamentioning
confidence: 99%
“…Psychiatric comorbidities in BMS were found in 22.2% to 71.6% [1,2,4,9], although the comorbidity of severe psychiatric disorders such as schizophrenia (0.8%) and bipolar disorders (1.6%) are rare [9]. The previous study revealed that depression and anxiety affect pain or unpleasant discomfort in BMS as well as chronic pain in the other body parts [10]. A negative aspect of pain perception itself also would induce anxiety and depression [11].…”
Section: Introductionmentioning
confidence: 97%
“…Patients with this syndrome are present to a variety of health professionals, such as oral surgeons, otolaryngologists and dermatologists (2). Since the pathophysiological origins of BMS remain unknown and comorbid psychiatric history are frequently observed, patients are occasionally referred to psychiatrists where its "medically unexplained" burning pain is regarded as a form of somatic symptom disorder (SSD) (3,4). Subsequently, these patients would be treated by psychopharmacotherapy with antidepressants or by other psychotherapeutic management (5).…”
Section: Introductionmentioning
confidence: 99%